Determination of inflationary behavior: A comparative analysis - M. Fahad Malik; Masood Sarwar Awan; Waseem Shahid Malik (Cogent Economics & Finance, 2022)
Standard theory of consumer behavior stands on the maxim of utility maximization. Optimizing behavior of consumer is achieved by maximization of utility subject to budget constraint. An increase in inflation that is not accompanied by proportionate increase in income can leave a consumer worse off. Therefore, it is imperative for consumers to have right assessment about inflation which in turn requires appropriate modelling of inflationary behavior. This study assesses efficacies of different versions of new Keynesian Phillips curve for capturing dynamics of CPI inflation. Estimation of different formulations of this curve is achieved by employing generalized method of moments. This choice of estimation technique is made to handle potential problem of endogeneity. Countries with different resource and market structures are included to evaluate and compare fitness of different formulations for different economies. Economies of Pakistan and Turkey represent developing economies, economy of South-Korea is incorporated for emerging market economy and economies of Canada, UK and US are included for developed economies. The results of this study reveal that internal as well as external factors are crucial for explaining inflationary behavior of developing economies. Whereas, dynamics of domestic inflation for advanced economies are mostly explained by internal factors.
Keywords: E12; E30; E31; 330; CPI inflation; new Keynesian Phillips curve; inflation dynamics; output gap